Teaching and learning innovations for distance learning in the digital era: a literature review - Li, Kam Cheong; Wong, Billy T. M.; Chan, Hon Tung (Frontiers in Education, 2023)
This paper presents a review study on teaching and learning innovations (TLIs) for distance learning in higher education, which involves substantial use of technology in its practice. The study covers 247 publications that were published from 2017-2022 and collected from Scopus to analyse the patterns and trends of TLIs for distance learning in higher education. The results show four main types of TLIs: educational technologies, teaching and learning approaches and activities, teaching and learning programmes, and assessment approaches and activities. They also reveal seven major pedagogical patterns in the TLIs, covering the learning of science through online laboratories, virtual and augmented reality, multimedia, gaming, collaboration, tasks/projects, and blended/hybrid/flipped learning. These findings suggest implications for distance learning, covering the use of online laboratories in science courses, promotion of virtual and augmented-based distance learning, encouragement of development, implementation, and the study of pedagogical approaches to distance learning, as well as the increase in interactivity in multimedia-based distance learning.